Analisis Deteksi Corona Virus Dengan Menggunakan Metode Forward Chaining - Zulla, Hafiz; Handoko, Divi (Universitas Harapan Medan, 2022)
This virus originated from Covid-19 or Corona Virus which has had an impact and symptoms that can kill humans with various complications of the disease they suffer. The problem that occurs is the panic of people who are reluctant to leave the house and are afraid of being exposed to the Corona Virus to carry out daily activities even to seek treatment at the hospital with symptoms that resemble the symptoms of exposure to the Corona Virus. coupled with the number of hospitals that are responsible for handling the Corona Virus which is a top priority for handling minor illnesses in general. Therefore, an expert system application for the diagnosis of Covid-19 or Corona Virus is needed. The expert system also requires a method that can operate, in this study the method used is Forward Chaining, the forward chaining method solves every symptom that appears and follows the next symptom in the same rule so that a decision tree is formed